THE EFFECT OF WASTEWATER OF DOMESTIC AND MEAT PROCESSING PLANT ON THE RIVER OF KARASU - Ümmühan DANIŞ (Pamukkale University Journal of Engineering Sciences, 1996)
The wastewaters of the slaughterhouse and meat processing plant in Erzurum city, which don't have any wastewater treatment plant is discharged to the Karasu river. The wastewater, especially occured during slaughtering and processing of meat, contained high level of COD, BOD5, total suspended solid, fat and grease and total solid. Therefore these wastewaters cause some environmental problems in the city. This paper presents the effect of wastewaters from resident area slaughterhouse, and meat processing plants on the river of Karasu. For this purpose some samples taken from eight different points around the river were analysed in order to obtain values of dissolved oxygen, BOD5, COD, total phosphorus, total kjeldahl nitrojen, total suspended solid, total solid, total volatile suspended solid, fat and grease, chlorides and coliform. From the results obtained, it is found out that the wastewaters from the slaughterhouse has the biggest pollutant effect in the river.